PENGARUH PENAMBAHAN SERAT GONI TERHADAP KUAT TEKAN DAN KUAT TARIK BETON - M Nuklirullah (Universitas Batanghari, 2018)
Concrete has less good properties, ie brittle so it is not strong enough to withstand tensile. To overcome the bad nature of the concrete can be done by adding fiber (fiber) on the concrete mix. The goal is to reinforce concrete with fiber that is spread uniformly into a concrete mix. The commonly used fibers are made of steel, polymer, or glass fiber. One type of fiber that can be used is roselle fiber which is the material of the burlap maker which belongs to the category of natural fiber. This research was conducted with the aim to know the compressive strength and tensile strength of concrete due to the influence of the addition of jute fiber. Variation of mixed fiber used is 0%, 1% and 3%. The test specimens were used in the form of a cylinder with a diameter of 15 cm and a length of 30 cm for a compressive strength test of 3 pieces and a tensile strength test of 3 pieces for each variation of the jute fiber mixture used. The results showed that with the addition of jute fiber decreased the value of workability. The unit weight of concrete decreases with increasing fiber content. Concrete strength and concrete tensile strength decrease with increasing jute fiber.Keywords: Concrete, Fiber, Compressive Strength, Tensile Strength